1999
DOI: 10.1038/sj.cdd.4400606
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppression without differentiation or apoptosis by antisense cyclin D1 gene transfer in K1735 melanoma involves induction of p53, p21WAF1 and superoxide dismutases

Abstract: In mammalian cells, terminal differentiation is mutually exclusive with proliferation. However, resistance to differentiation-inducing therapy requires alternative strategies to control poorly responsive tumors. We now show that retroviral transfer of the antisense cyclin D1 gene to differentiationrefractory K1735 melanoma leads to loss of in vivo tumorigenicity, shortened replicative ability, induction of the tumor suppressor p53 protein and of the cdk-inhibitor p21WAF1, increased b-galactosidase pH 6.0 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Furthermore, mouse embryo fibroblasts deficient in both CDK4 and CDK6 are able to proliferate, albeit slower than wild-type counterparts (39); hence, it is possible that cyclin D-CDK2 complexes play an important role in proliferation. In summary, our data show that cyclin D3 is an important regulator of melanoma cell proliferation and together with other studies (11,43) highlight therapeutic targeting that more than one D-type cyclin may be necessary to efficiently block melanoma growth.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, mouse embryo fibroblasts deficient in both CDK4 and CDK6 are able to proliferate, albeit slower than wild-type counterparts (39); hence, it is possible that cyclin D-CDK2 complexes play an important role in proliferation. In summary, our data show that cyclin D3 is an important regulator of melanoma cell proliferation and together with other studies (11,43) highlight therapeutic targeting that more than one D-type cyclin may be necessary to efficiently block melanoma growth.…”
Section: Discussionsupporting
confidence: 83%
“…We found that 4‐NC was able to induce an increase of SOD activity in fibroblasts but not in melanomas. An increase of antioxidant enzymes can be associated with suppression of tumorigenicity and metastatic ability in some tumors (Rieber and Rieber, 1999). Therefore, the increased SOD activity in fibroblasts upon 4‐NC treatment might explain the resistance of these cells to 4‐NC, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Church et al (1993) showed that transfecting MnSOD cDNA into human melanoma cells increased enzyme expression and suppressed their malignant phenotype. Rieber and Rieber (1999) reported the retroviral transfer of the anti-sense cyclin D1 gene to differentiation-refractory K1735 melanoma, which, among other changes, leads to the loss of tumorigenicity in vivo and a greater SOD/peroxidase ratio; both being associated with replication senescence. Also, transfection of a human MnSOD cDNA into the promotable mouse epidermal cell line JB6 clone41 elicits an overexpression of the enzyme and induces a slower growth rate of the cells (Amstad et al, 1997).…”
Section: Discussionmentioning
confidence: 99%